Strategi dan Arah Pembangunan Kualitas Manusia - Novliza Eka Patrisia; Faizal Anwar (JOPPAS: Journal of Public Policy and Administration Silampari, 2020)
The purpose of this study is to explain the strategy and direction of human quality development from the perspective of public administration. The method used is descriptive method, which is describing human quality development strategies from various literatures related to human resource development (HR). The results of the literature review show that the development of quality human bureaucracy is a necessity to be able to provide satisfying public services. Conclusions, Strategies and directions that need to be done by the HR manager is to improve physical and psychological quality. Keywords: Development Strategy, Human Resources